Attoampere Nanoelectrochemistry. Issue 29 (13th June 2021) - Grall, Simon; Alić, Ivan; Pavoni, Eleonora; Awadein, Mohamed; Fujii, Teruo; Müllegger, Stefan; Farina, Marco; Clément, Nicolas; Gramse, Georg
Abstract: Electrochemical microscopy techniques have extended the understanding of surface chemistry to the micrometer and even sub‐micrometer level. However, fundamental questions related to charge transport at the solid‐electrolyte interface, such as catalytic reactions or operation of individual ion channels, require improved spatial resolutions down to the nanoscale. A prerequisite for single‐molecule electrochemical sensitivity is the reliable detection of a few electrons per second, that is, currents in the atto‐Ampere (10 −18 A) range, 1000 times below today's electrochemical microscopes. This work reports local cyclic voltammetry (CV) measurements at the solid‐liquid interface on ferrocene self‐assembled monolayer (SAM) with sub‐atto‐Ampere sensitivity and simultaneous spatial resolution < 80 nm. Such sensitivity is obtained through measurements of the charging of the local faradaic interface capacitance at GHz frequencies. Nanometer‐scale details of different molecular organizations with a 19% packing density difference are resolved, with an extremely small dispersion of the molecular electrical properties. This is predicted previously based on weak electrostatic interactions between neighboring redox molecules in a SAM configuration. These results open new perspectives for nano‐electrochemistry like the study of quantum mechanical resonance in complex molecules and a wide range of applications from electrochemical catalysis to biophysics. Abstract : This work presents a novel technique for nanoscale electrochemistry measurements with attoampere current resolution and local cyclic voltammogram measurements. It opens the perspective for a wide range of applications in biophysics, molecular electronics, and electrochemical measurements at the nanoscale.